The effect of oxygen pickup during selective laser melting on the microstructure and mechanical properties of Ti–6Al–4V lattices - M. Velasco-Castro; E. Hernández-Nava; I.A. Figueroa; I. Todd; R. Goodall (Heliyon, 2019)
Additive manufacturing techniques such as Selective Laser Melting (SLM) can produce complex shapes with relatively thin sections and fine detail. However, common materials for the process, such as Ti–6Al–4V, have microstructure and properties that are sensitive to the pickup of interstitial impurities, such as oxygen, which the material will be exposed to during the process. This problem would be especially severe for parts with thin sections, where surface effects can be more significant, and where poor properties may coincide with locally-elevated stress. Here we explore the effects of oxygen level in thin sections with the use of lattice materials (materials which can be considered to consist exclusively of near-surface material). Oxygen levels are artificially raised using repeated melting passes to result in more pickup, leading to significantly reduced ductility and hence reduced strength measured in compression. A ductile to brittle transition in strut failure mechanism is found with increasing number of melting passes, with significant modification in chemistry and crystallographic structure, despite the presence of a similar fine plate-like microstructure throughout.